The impact of renewable energy on economic well-being of Malaysia: fresh evidence from auto regressive distributed lag bound testing approach - Haseeb, Muhammad; Zainal Abidin, Irwan Shah; Muhammad Adnan Hye, Qazi; Hartani, Nira Hariyatie (2019)
This present study examines the role of renewable energy in influencing economic well-being in Malaysia. We used annual data over the period of 1980 to 2016 in order to apply recent econometrics. The study used renewable energy and economic growth as a proxy of economic well-being to examine the long run connection between renewable energy and economic well-being. The results of ARDL bound testing approach confirm the valid long-term connection among renewable energy and economic well-being in Malaysia. Furthermore, the results indicate that renewable energy have significant and positive impact on economic well-being in short and long run. It is therefore recommended that the policymakers are required to focus on the green energy generation sector by increasing renewable energy production from the existing sources.